2022
DOI: 10.26650/iuitfd.1031447
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Age, Sex, and Socio-Economic Status on Serum Vitamin B12, Folate Concentration and Iron Status in Turkish Children: A Cross-Sectional Study

Abstract: Objective: The aim of this study is to evaluate the effects of age, sex, and socio-economic status (SES) on concentrations of vitamin B12 (vit-B12), folate, iron, and ferritin through the pediatric age span, and to show the relationship of these nutrients with blood count parameters such as hemoglobin (Hb), hematocrit (Hct), mean corpuscular volume (MCV), and red cell distribution (RDW). Material and Method:The study comprised of 30,504 venous blood samples (54.5% of girls and 45.5% of boys). The study group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
2
3
1
Order By: Relevance
“…In the most extensive cohort study conducted in our country, involving the analysis of blood samples from 30,504 individuals, no significant correlation was detected between B12 levels and gender [20]. However, smaller-scale cohort studies have indicated a predominance of males [20][21][22][23][24]. In contrast to these findings, our research revealed a prevalence of B12 deficiency among females across all age brackets.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In the most extensive cohort study conducted in our country, involving the analysis of blood samples from 30,504 individuals, no significant correlation was detected between B12 levels and gender [20]. However, smaller-scale cohort studies have indicated a predominance of males [20][21][22][23][24]. In contrast to these findings, our research revealed a prevalence of B12 deficiency among females across all age brackets.…”
Section: Discussioncontrasting
confidence: 99%
“…The rate of 30% in our study is quite close to the 27% reported by Eroğlu et al [20]. This indicates that the results of the first two largest studies with the most extensive dataset in our country are consistent with each other, demonstrating that the rate of B12 supplementation need in Turkey ranges between 27% and 30%.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similarly, in another study conducted in Amasya province and published in 2023, the rate of B12 deficiency was determined to be 18% among 240 cases [4]. [20].…”
Section: Discussionmentioning
confidence: 97%